Pengaruh Variasi Proses Pirolisis Terhadap Nilai Kalor Biopelet Berbahan Baku Sabut Kelapa - Alfi Ferizqo Munawar; Sigit Mujiarto; Sigit Joko Purnomo (Pusat Riset dan Inovasi Nasional, 2024)
Biopellets can be used as a heat generator in private homes and small businesses. Biopellets are made by compressing and molding with adhesive. Based on this composition, it shows that coconut fiber has the potential to be used as biopellet charcoal fuel. However, the calorific value of coconut fiber is still relatively low. The way to increase the calorific value of coconut fiber is through the pyrolysis process. The advantage is also that it reduces the water content of the product, making it less likely to absorb moisture from the air. One use of charcoal produced from the pyrolysis process of coconut fiber as household or industrial fuel is as biopellets. The method used in this research is an experimental method on the effect of variations in the temperature of the pyrolysis process made from coconut fiber in making biopellets to determine the effect of variations in pyrolysis temperature, namely 300°C, 350°C and 400°C on the calorific value, the effect of variations on fixed carbon, and burning rate of coconut fiber biopellets which can be used as an alternative energy source.